Residual stone fragments: systematic review of definitions, diagnostic standards - Çavdar, O. F.; Aydin, A.; Tokas, T.; Tozsin, A.; Gadzhiev, N.; Sönmez, M. G.; Tekeli, R.; Ortner, G.; Kallidonis, P.; Akgül, B.; Knoll, Thomas; Bianchi, G.; et al. (World journal of urology, 2025)
Residual stone fragments (RSFs) remain a determining factor for evaluation of outcome an intervention for management of renal tract stones. However, there is a lack of consensus on size, location, diagnosis and management of RSF. This systematic review aims to assess definitions and diagnostic approaches to RSF across urolithiasis treatment modalities while standardizing their definition and diagnosis through a systematic review, stratifying RSF patients into risk groups, and proposing an approach for management.